Makulopatia słoneczna u Leona Wyczółkowskiego? - Kałużny, Józef; Markowski, Dariusz; Kałużny, Bartłomiej; Sikorski, Bartosz (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Noted Polish painter, Leon Wyczółkowski, during his long-standing in Ukraine used to paint pictures gazing directly at the sun in order to intensify visual sensations. Damage to the eyes caused by sunlight induced him to become a patient of a famous ophthalmologist in Kiev. Past disease led to blue color vision impairment just like it happen to people who previously suffered from solar maculopathy. We suppose, it could gradually force the artist to resign from color painting and to take up drawing.